3‐Formyl‐BODIPY Phenylhydrazone as a Chromo‐Fluorogenic Probe for Selective Detection of NO2 (g). Issue 25 (4th May 2016) - Juárez, L. Alberto; Costero, Ana M.; Parra, Margarita; Gaviña, Pablo; Gil, Salvador
Abstract: A new colorimetric and fluorogenic probe, based on a 3‐formyl boron dipyrromethene (BODIPY) phenylhydrazone, for the sensitive and selective detection NO2 (g) has been prepared. The probe in solution experiences a remarkable hypsochromic shift of its absorption and fluorescence emission bands in the presence gaseous NO2 (g), leading to limits of detection of few ppb. The probe also works in the solid phase, adsorbed on filter paper strips, or chemically immobilized on the surface of silica nanoparticles, with limits of detection to the naked eye of about 0.5 ppm. Abstract : Get that gas ! A colorimetric and fluorogenic probe, based on a 3‐formyl boron dipyrromethene (BODIPY) phenylhydrazone, for the sensitive and selective detection NO2 (g) has been prepared (see scheme). The probe in solution experiences a remarkable hypsochromic shift of its absorption and fluorescence emission bands in the presence gaseous NO2 (g), leading to limits of detection of few ppb.